PENGARUH MEDIA FILM DALAM MENINGKATKAN HASIL BELAJAR PESERTA DIDIK KELAS V PADA MATA PELAJARAN SEJARAH KEBUDAYAAN ISLAM DI MIN 10 BANDAR LAMPUNG - agus sofiana, Ira (Institut Agama Islam Riyadlatul Mujahidin Ngabar (IAIRM) Ponorogo, 2024)
Media is one of the elements that play an important role in the implementation of the teaching and learning process. The use of learning media in the teaching and learning process can increase understanding, present data in an interesting way, facilitate learning and condense information. What's more, film media is a medium that combines audio, visual, and motion simultaneously so that it can attract students' learning. This study aims to determine the effect of film media in improving the learning outcomes of fifth grade students in SKI subjects at MIN 10 Bandar Lampung. The research method used is Quasi Experiment. The research design used in this Quasi experiment was the pretest and posttest Control Group Design. This research was conducted at MIN 10 Bandar Lampung which consisted of 2 classes, namely the experimental class (VB) and the control (VA). Data collection techniques using tests and documentation. The instrument used is an objective test to measure student learning outcomes on cognitive aspects. After the objective test data is collected, the processing is carried out by means of statistical analysis using the normality test, homogeneity test and t test. From the research results it is known that the learning outcomes of students after the learning process using film media average value is 76.08 while without using film media the average value is 72.08. The t test for the final test score obtained tcount>ttable, namely 2.853 > 1.671 at a significance level of 5% or 0.05. According to the test criteria, it means that Ha is accepted and Ho is rejected. This shows that there is a significant difference between learning outcomes using film media and learning outcomes without using film media. Thus the use of film media has an effect on improving the learning outcomes of fifth grade students in SKI subjects at MIN 10 Bandar Lampung.